Extracellular Vesicles and Cancer Therapy: Insights into the Role of Oxidative Stress - Jenni Ho; Luksana Chaiswing; Daret K. St. Clair (MDPI AG, 2022)
Oxidative stress plays a significant role in cancer development and cancer therapy, and is a major contributor to normal tissue injury. The unique characteristics of extracellular vesicles (EVs) have made them potentially useful as a diagnostic tool in that their molecular content indicates their cell of origin and their lipid membrane protects the content from enzymatic degradation. In addition to their possible use as a diagnostic tool, their role in how normal and diseased cells communicate is of high research interest. The most exciting area is the association of EVs, oxidative stress, and pathogenesis of numerous diseases. However, the relationship between oxidative stress and oxidative modifications of EVs is still unclear, which limits full understanding of the clinical potential of EVs. Here, we discuss how EVs, oxidative stress, and cancer therapy relate to one another; how oxidative stress can contribute to the generation of EVs; and how EVs' contents reveal the presence of oxidative stress. We also point out the potential promise and limitations of using oxidatively modified EVs as biomarkers of cancer and tissue injury with a focus on pediatric oncology patients.